Data-driven demand analysis and design reliability study of critical components of complex products. - Zhan Meng; Zhenggang Wang; Dapeng Gao; Wei Lu (PLoS ONE)
Distinguished from the traditional general framework of product design, under the background of digital intelligence, the complex product design method presents the characteristics of rapid iteration and high degree of integration, and adopts the simulation and modeling technology, advanced production methods, etc. to further improve the quality and reliability of complex product design. Therefore, the demand analysis and design reliability study of critical components of complex products need to consider the sustainability, resources and economy of design, manufacturing and service. In this paper, starting from the product requirement analysis, the Kano-QFD model is used to clarify the requirement identification path of the critical components of complex products and ensure that the quality characteristics of the critical components of complex products are consistent with the customer requirements. The multi-dimensional characteristics of product design parameters, manufacturing process and quality are integrated to construct a design manufacturing analysis (DMA) model, which it's based design reliability analysis method for critical components of complex products. Finally, the method proposed in this article was validated by taking the demand analysis and design reliability of critical components of automotive engines as an example. The study shows that the method proposed in this paper is highly compatible with the practice of complex product design and manufacturing at the early stage, and the method proposed in this paper also can provide product design and quality management reference for the research and development and manufacturing personnel of complex products to meet the changing needs and challenges of complex products.